The Juridical Analysis of the Term of Banking Liability Loan Ownership of FLPP Prosperity - Muhammad Firdaus (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
Procedures for granting Subsidized Housing Loan facilities by Bank Mandiri Semarang Pahlawan Area, namely Submission of files; Loan file investigation; Interview 1; On the spot; Interview 2; Credit decisions; Signing of credit contracts/other agreements; Credit realization; and Distribution/auction house. The regulation of the time period regarding the SKMHT Deed in the Mortgage Law clearly states that the SKMHT cannot be withdrawn or cannot be terminated for any reason, except because the power of attorney has been exercised or because the term has expired. The period of use of SKMHT in the provision of Subsidized Housing Loan facilities by Bank Mandiri Semarang Pahlawan Area in its implementation is followed by the Deed of Granting Mortgage Rights (APHT). This type of research is normative or juridical normative, namely by researching library materials and secondary materials, while the nature of this research is analytical descriptive. Sources of data in this study is secondary data. The data collection used in writing this thesis is through literature research techniques. The method of data analysis carried out by the author is a qualitative approach. It is expected that the Bank Mandiri Area Semarang Pahlawan should be objective in selecting prospective debtors so that the benefits of the Subsidized Housing Credit program can be felt, it is hoped that the government regarding the provisions of Article 15 paragraph (3) and (4) UUHT to be reviewed because the SKMHT period is fairly short and not commensurate with the length of the process of issuing the certificate of land rights and it is hoped that the Bank Mandiri Area Semarang Pahlawan in the use of SKMHT in the provision of Subsidized Housing Credit facilities should be followed by APHT in its implementation.